PERANCANGAN SISTEM OTOMATISASI PADA MESIN GRAVITY CASTING - , ADITYA PRAKOSO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In the Industrial world, now optimalization is important in the field of production. Therefor SEI Indonesia as the industry engaged in sevices engineering help provide a solution for this problem. gravity casting machine is a machine use to casting process especially for make intake manifold when the casting process using gravity process. Because the machine worked for mass product so the machine must be operated continuously and process product must be stable. And then the gravity casting must be otomatization for operating so the efficiency for working machine and the product is maximaze too. The otomatization for this machine use for PLC as controlling the machine cycle which consists of cope and drag closed process, the molten metal casting process(rotating process),the last cope and drag opened and tool was taken. All of process can be calculating with a certain time with PLC. The result otomatization is important for decrease production time and maximaze the total production compared with manual processes.